PENDIDIKAN NILAI, BUDAYA DAN KARAKTER DALAM PEMBELAJARAN MATEMATIKA DASAR PADA SD/MI - Agus Setiawan; Ika Ratih Sulistiani (Universitas Islam Malang, 2019)
Value, culture and character education is an effort to improve the quality of the process and learning outcomes that lead to the formation of the character of students who are characterized by national culture. These cultural values and characters are the pride of the nation and make the nation known by other nations as a nation that has a distinctive Indonesian character. Education has a function in developing cultural values and past achievements into a proud element for the present and future life so that it becomes a strong foundation for national character. Value education, culture and national character are important points that must emerge in the learning process in the classroom. Integration of the three in the learning process, especially mathematics learning, is intended as a process of introducing values and culture, facilitating the acquisition of awareness of the importance of values and culture in the behavior of students through daily learning processes that take place both inside and outside the classroom on all math subjects. Thus, mathematics learning activities, in addition to making students master competencies (material taught in mathematics) are targeted, also to make students know, care, and internalize cultural and character values in everyday behavior